Development of a rice-mongo-peanut based kroepeck - Young, Ma. Theresa P.
ABSTRACT Rice-mongo-peanut based kroepeck was developed as a high protein snack food. A protein snack food. A protein content of 11% was the basis for this newly developed product. Proximate composition and sensory evaluation were done to determine the best formulated sample. A two-month storage stability study was conducted. Moisture content, water activity and thiobarbituric acid number were monitored for the duration of the storage stability study. The microbiological quality of the product was also monitored during the storage period.Sensory evaluation was conducted in terms of odor, flavor, seasoning and general acceptability. Results showed no significant changes in sensory attributed of the product during storage.